A review on insulin-producing beta cell: regenerative role of drugs acting on DYRK1A, GLP-1 and DPP-4 receptors - Mahmood, Nyrit (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.